A Novel Image Mosaicking Algorithm for Wireless Multimedia Sensor Networks. (5th October 2013) - Li, Zhiyuan; Kong, Weiting; Zhan, Yongzhao; Bi, Junlei
The wisdom tourism is an important application of internet of things industry, and many cities in China have paid attention to the development of wisdom tourism, such as the national historic city of Zhenjiang. How to take advantage of the cooperation among sensor nodes to obtain the panoramic information of scenic spots is a challenging issue for the wisdom tourism. However, the existing image mosaic algorithms are not suitable for wireless multimedia sensor networks (WMSNs) due to the resource-constrained multimedia sensor nodes, such as energy, computing, and storage space. And hence an image mosaic algorithm based on phase correlation and weighted average (IMBPW) is proposed in this paper. The IMBPW algorithm uses the phase correlation based on Fourier transform to achieve the registration of translation, rotation, and scaling images. After the image registration, the adaptive weighted average algorithm is proposed to do the image fusion. The simulation experiments show that compared with homogeneous algorithms, the IMBPW algorithm has higher real-time and fast convergence speed. Furthermore, the simulation results also show that the proposed algorithm can improve the accuracy of image registration, reduce the complexity of the image mosaic, and prolong the network lifetime while providing better image quality.